Uncover Student’s Alternative Conception in Acid-Base Theory Using a Modified Certainty of Response Index Instrument - Satya Sadhu (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2019)
Several researchers have documented alternative conception concerning chemistry subject on high school, for instance, in acid base theory. Acid base theory is a basic concept to learn other level of concept but the volume of research on student’s alternative conception on acid-base has increased tremendously. It reveals that the complexity of acid base concept can tend to create student’s alternative conception. Futhermore, this study addressed to reveal the student’s alternative conception in acid-base theory using modified certainty of response index. The modified CRI test were administered to 148 participants who enrolled in the high school in Mataram, Indonesia. In addition, several students were interviewed in order to scrutinize their alternative conceptions. The findings revealed a number of student’s alternative conceptions in acid-base theory. Student’s alternative conceptions occurred because they partially understand the concept and tend to memorize it. The results have suggestion that a substantial review of teaching is needed to reduce student’s alternative conception